Serum biomarkers and their relationship to axial spondyloarthritis associated with inflammatory bowel diseases - Ondrejčáková, L; Gregová, M; Bubová, K; Šenolt, L; Pavelka, K (Autoimmunity reviews, 2024)
Spondyloarthritis (SpA) constitute a group of chronic inflammatory immune-mediated rheumatic diseases characterized by genetic, clinical, and radiological features. Recent efforts have concentrated on identifying biomarkers linked to axial SpA associated with inflammatory bowel disease (IBD), offering predictive insights into disease onset, activity, and progression. Genetically, the significance of the HLA-B27 antigen is notably diminished in ankylosing spondylitis (AS) associated with IBD, but is heightened in concurrent sacroiliitis. Similarly, certain polymorphisms of endoplasmic reticulum aminopeptidase (ERAP-1) appear to be involved. Carriage of variant NOD2/CARD15 polymorphisms has been demonstrated to correlate with the risk of subclinical intestinal inflammation in AS. Biomarkers indicative of pro-inflammatory activity, including C-reactive protein (CRP) along with erythrocyte sedimentation rate (ESR), are among the consistent predictive biomarkers of disease progression. Nevertheless, these markers are not without limitations and exhibit relatively low sensitivity. Other promising markers encompass IL-6, serum calprotectin (s-CLP), serum amyloid (SAA), as well as biomarkers regulating bone formation such as metalloproteinase-3 (MMP-3) and Dickkopf-related protein 1 (DKK-1). Additional candidate indicators of structural changes in SpA patients include matrix metalloproteinase-3 (MMP-3), vascular endothelial growth factor (VEGF), tenascin C (TNC), and CD74 IgG. Fecal caprotein (f-CLP) levels over long-term follow-up of AS patients have demonstrated predictive value in anticipating the development of IBD. Serologic antibodies characteristic of IBD (ASCA, ANCA) have also been compared; however, results exhibit variability. In this review, we will focus on biomarkers associated with both axial SpA and idiopathic intestinal inflammation, notably enteropathic spondyloarthritis.
Keywords: HLA-B27 Antigen; idiopatické střevní záněty; C-reaktivní protein; C-Reactive Protein; Spondylitis, Ankylosing; ankylózující spondylitida; Humans; HLA-B27 antigen; Biomarkers; Inflammatory Bowel Diseases; Axial Spondyloarthritis; Leukocyte L1 Antigen Complex; biologické markery; axiální spondyloartritida; lidé; leukocytární L1-antigenní komplex